Laboratory quality stepwise implementation tool: National reference TB laboratory of Iran - Ali Naghi Kebriaee; Donya Malekshahian; Mojtaba Ahmadi; Parissa Farnia (International Journal of Mycobacteriology, 2015)
Background and objective: During recent years, the World Health Organization (WHO) proposed new software for improving the tuberculosis (TB) laboratory services. The protocol is known as “quality stepwise implementation tool” and is based on enforcement of quality assurance services through accreditation by the International Organization for Standardization (ISO) 15189. As a national reference TB laboratory (NRL) of Iran, the benefit and challenges of implementing this standard were analyzed. Material and Methods: The investigation was a cross-sectional study and was underlined by the committee of the Quality Management System (QMS) in the NRL. The required information was collected in two steps: first, the QC form that contains 334 quality questions (designed by WHO) was filled out. These questions determine 12 main organizational blocks of laboratory (facilities and safety1, organization and personnel2, documents and records3, management reviews4, client management and customer service5, equipment6, internal audit7, purchasing and inventory8, information management9, process control and internal / external quality management10, corrective actions occurrence11, and incident management and process improvement12). The minimum rating of laboratories is stated to be from 55% to a maximum of 95%. In the second step, using the quality stepwise implementation tool, these blocks were in four phases, and 41 steps were analyzed. The data were compared using Fisher's Exact test and Pearson Chi-Square. Results: In the period 2013–2014, the rate of OMS in three focal points (pre-analytical, analytical, and post-analytical) in the NRL was in the range of 80–100%; whereas in previous years the rate ranged from 48% to 79%. Therefore, through QMS the NRL scores had reached a higher level. Based on available results, the NRL-assigned score was a 5-star rating. Conclusions: As the internal score of NRL reaches 5, an international evaluation of accreditation scheme is sought. This is the first investigation that used the quality stepwise implementation tool in Iran.